The Symbolic Meaning of Pamona Traditional Wedding Dress a Semiotic Study of Charles Sanders Peirce - Feinne Virensya Mapule; Agustan; Juniati; Syamsuddin; Nur Halifah (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
Pamona traditional wedding clothes are part of the cultural heritage that contains various systems of signs and symbolic values that reflect the life view of the Pamona people. Although a number of studies have addressed the traditional wedding traditions of Pamona, studies that specifically examine the symbolic significance of elements of Pamona traditional wedding dress based on the semiotic perspective of Charles Sanders Peirce are still relatively limited. This condition results in the cultural meaning contained in every element of Pamona traditional bridal clothing that has not been comprehensively documented and interpreted in scientific studies. Therefore, this study aims to describe the symbolic meaning contained in Pamona's traditional wedding dress. This study uses a descriptive qualitative approach by involving four main informants, namely Pamona traditional leaders, traditional clothing artisans, and community elders who have in-depth knowledge of Pamona traditional clothing. Data collection was carried out through observation, in-depth interviews, and documentation. The data obtained were analyzed using the Miles and Huberman analysis model and studied through the Charles Sanders Peirce semiotic framework. The results of the study show that each element in the Pamona traditional wedding dress contains a symbolic meaning that reflects the cultural values of the Pamona people. In men's clothing, siga is interpreted as a symbol of leadership and social status, while guma symbolizes responsibility, work ethic, and protection of the family. Meanwhile, in women's clothing, bingka ornaments represent responsibility and concern in family life, while areca nut ornaments symbolize loyalty and commitment in marital relationships. Analysis of the relationship between representation, object, and interpretation shows that these symbols function as a means of transmitting cultural values, social norms, and the collective identity of the Pamona people. This research contributes to strengthening scientific documentation on the symbolism of Pamona traditional wedding dresses, expanding the treasures of local cultural semiotics studies, and supporting efforts to preserve the cultural heritage and customary knowledge system of the Pamona people for the sustainability of future generations